Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire - Gómez, Samuel; Gerber, Ray; Fuentes-Reinés, Juan Manuel (Zootaxa, 2017)
The history surrounding the identity of Cletocamptus albuquerquensis (Herrick, 1894) and C. dominicanus Kiefer, 1934 is very complex. This complexity has been exacerbated by incomplete, and in some cases erroneous, original descriptions of these two species. Also, new records from other locations did not describe the significant characters needed to clearly delineate them. This led several authors to consider C. dominicanus as a synonym of C. albuquerquensis, among other taxonomical considerations regarding, for example, the status of Marshia brevicaudata Herrick, 1894. Inspection of biological material from Saskatchewan (southern Canada), Wyoming (central US), Trinidad and Tobago, and the British Virgin Islands, identified by other researchers as C. albuquerquensis, as well as of newly collected material from Great Salt Lake (Utah, central US), Puerto Rico, Culebra Island, Vieques Island, St. John Island (US Virgin Islands), San Salvador (Bahamas), and Santa Marta (Colombia), revealed that C. albuquerquensis and C. dominicanus are distinct and identifiable species, distributed in a more restricted area than previously thought. Additionally, we describe a new species, C. tainoi sp. nov., from St. John Island (US Virgin Islands), and we propose another new species, C. chappuisi sp. nov., for two males from Bonaire previously identified as C. albuquerquensis. Finally, we give some observations on tube-pore-like structures, previously overlooked, on the endopod of the male leg three.